ПЕРЕПРОГРАМУВАННЯ МЕТАБОЛІЗМУ ГЛЮКОЗИ В КЛІТИНАХ РАКУ МОЛОЧНОЇ ЗАЛОЗИ ЛЮДИНИ ПІСЛЯ СПІВКУЛЬТИВУВАННЯ З BIFIDOBACTERIUM ANIMALIS - KOZAK, T.; LYKHOVA, O.; CHEKHUN, V. (PH Akademperiodyka, 2025)
Background. The ability to reorganize metabolic processes is one of the key properties of malignant cells necessary to ensure high energy needs, survival, proliferation, metastasis, and resistance to anticancer drugs. Lactic acid bacteria, in particular Bifidobacteria, are important elements of the tumor microenvironment in breast cancer (BC) and, as active lactate producers, can influence the metabolic phenotype of malignant cells. Aim. To study the effect of B. animalis on some components of glucose metabolism pathways and the expression of proteins associated with this process in human BC cells of different molecular subtypes. Materials and Methods. The study was performed on human BC cells of the T-47D, MCF-7 (luminal subtype), and MDA-MB-231 (basal subtype) lines and live culture of Bifidobacterium animalis subsp. lactis (B. animalis). A colorimetric enzymatic technique, flow cytometry, immunocytochemical analysis, and cell viability trypan blue exclusion assay were used in the study. Results. Co-cultivation of BC cells with B. animalis resulted in a significant (p < 0.05) increase in the glucose consumption rate by 1.2—4.7 times, lactate production by 15—115%, and LDH activity by 15—160% in BC cells compared to control cells. The most pronounced changes were observed in BC cells of the luminal subtype where they were accompanied by an increase in the expression of the GLUT1 glucose transporter by 30—80% compared to control cells. Also, after co-cultivation with B. animalis, we detected an increased expression of the STAT6 transcription factor in BC cells of all three lines. Conclusions. Co-cultivation of BC cells with B. animalis is accompanied by an increase in glycolysis. B. animalis affected not only the biochemical components of the glucose metabolism pathway but also the expression levels of STAT6, GLUT1, and insulin receptor.